Structure, Capacity or Power? Explaining Salience in EU Decision‐Making1. (22nd November 2013) - Leuffen, Dirk; Malang, Thomas; Wörle, Sebastian
Abstract Salience as the intensity of interest is a key explanatory factor of European Union decision‐making. In this article, the ability of three explanatory models to explain the realized values of Member States' salience is hypothesized and tested. On the basis of the DEU II data, the analysis shows that a mixture of national interest group heterogeneity and membership length has the highest predictive power. The results support the liberal intergovernmentalist claim that domestic interests determine European decision‐making.